Retroperitoneal Laparoscopic Management of Paraganglioma: A Single Institute Experience - Xu, Weifeng; Li, Hanzhong; Ji, Zhigang; Yan, Weigang; Zhang, Yushi; Zhang, Xuebin; Li, Qian (PloS one, 2016)
To explore the feasibility and safety of retroperitoneal laparoscopic resection of paraganglioma (RLPG) in a large study population. In a six-year period, 49 patients with primary retroperitoneal paragangliomas (PG) underwent retroperitoneal laparoscopic surgery in a single center. Medical records were reviewed, and collected the following data, which were clinical characteristics, perioperative data (operative time, estimated blood loss, intraoperative hemodynamic changes, intraoperative and postoperative complications, and open conversions), and follow-up data (recurrence or distant metastases). All PGs were removed with negative tumor margin confirmed by postoperative histopathology. The operative time of RLPG was 101.59±31.12 minutes, and the estimated blood loss was 169.78±176.70ml. Intraoperative hypertensive and hypotensive episodes occurred in 25 cases and 27 cases, respectively. Two open conversions occurred. Two intraoperative complications occurred but were successfully managed endoscopically. Postoperative complications were minor and unremarkable. No local recurrence or distant metastasis were observed during the follow-up period. Our experience indicates the feasibility and safety of resection of PGs in a relatively large study population.